Targeting Suppressive Oligonucleotide to Lymph Nodes Inhibits Toll-like Receptor-9-Mediated Activation of Adaptive Immunity - Yu, Chunsong (Pharm Res, 2018)
PURPOSE: This paper aims to investigate the immunoinhibitory properties of a lymph nodes-targeting suppressive oligonucleotide (ODN) for the potential treatment of autoimmune diseases or chronic inflammation. METHODS: Synthetic suppressive ODN engineered with an albumin-binding diacyl lipid at the 5’-terminal (lipo-ODN) was synthesized. In vitro and in vivo experiments were designed to compare the immune suppressive properties of lipo-ODN and unmodified ODN. Cellular uptake and distribution, inhibition of Toll-like receptor (TLR) activation, lymph nodes (LN) draining, and the suppression of antigen-specific immune responses in an ovalbumin protein model was investigated. RESULTS: Compared to unmodified ODN, lipid functionalized suppressive ODN demonstrated enhanced cellular uptake and TLR-9 specific immune suppression in TLR reporter cells. Additionally, injection of a low dose of lipid-modified suppressive ODN, but not the unconjugated ODN, accumulated in the draining LNs and exhibited potent inhibition of antigen-specific CD8+ T cell and B cell responses in vivo. CONCLUSIONS: Targeting suppressive ODN to antigen presenting cells (APCs) in the local LNs is an effective approach to amplify the immune modulation mediated by ODN containing repetitive TTAGGG motif. This approach might be broadly applicable to target molecular adjuvants to the keyimmune cells in the LNs draining from disease site, providing a simple strategy to improve the efficacy of many molecular immune modulators.